Peranan Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru - Dian Ayuningtyas (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
This paper aims to know and reveal the role of headmaster leadership in increasing teacher performance. The quality of headmaster leadership highly determines the good or bad performance of a teacher. However, actually, there are a number of factors inhibiting to meet the quality leadership of a headmaster, like low mentality of the headmaster which is indicated by low motivation and passion to improve the school, lack of insight, less brave to make a change, and numerous other factors that hamper the birth of professional headmaster to improve education quality. Teacher performance is not only influenced by his/her qualification and competence as a teacher but is also affected by other factors that take a role either directly or indirectly such as school culture. It takes cooperation, coordination, and mutual agreement to create a conducive school culture to actualize the goals and a better school quality.